Reciprocal interactions between the neuroendocrine and immune systems during inflammation. - Chikanza, I; Grossman, AB (2000)
The neuroendocrine and immune responses to inflammatory stress represent important integrated physiologic circuits for the regulation of inflammation whose basis has been reviewed. Proinflammatory cytokines such as IL-1 beta, TNF alpha, and IL-6 released from inflammatory foci initiate a local inflammatory response and travel by way of the blood-stream to the central nervous system, where they trigger a variety of neuroendocrine counterregulatory mechanisms. There is an important NEI loop. Stimulatory signals are received by the neural systems from inflammatory foci and are transduced by the hypothalamus, thereby initiating a complex hormonal and cytokine cascade of reactions aimed at modulating inflammation and returning the organism to normal physiologic homeostasis once the trigger has been neutralized. Conversely, a number of mechanisms that modulate the anti-inflammatory activity of the neuroendocrine responses to inflammation are also activated. Defects in the neuroendocrine-immune interactions can profoundly affect the susceptibility to developing chronic inflammatory disease and influencing survival after bacterial infections. The NEI loop has important pathophysiologic implications for disease processes.